PERUBAHAN KARAKTERISTIK FISIK TEH HITAM SELAMA OKSIDASI ENZIMATIS PADA PROSES PENGGILINGAN CTC - Gilang Yoga Pratama; M.Sc, Desiana Nuriza Putri; Roberto Danieli; Elfi Anis Saati (Universitas Islam Balitar, 2022)
Black tea in the manufacturing process undergoes an enzymatic oxidation process. The process of enzymatic oxidation has occurred when tea undergoes a milling process. The study aimed to find out and analyze the black tea powder results from milling. This study used a RAK analysis design (Group Random Design) with 4 treatments (P1) rotor vane, (P2) roll 1 TPI 8, (P3) roll 2 TPI 10, and (P4) roll 3 TPI 10. The observed test parameters include form analysis, temperature analysis, sensory testing, and monitoring of the performance efficiency of the milling machine. The results of the form analysis showed that the treatment (P1), (P2), (P3), (P4) changed the entire shape of the particles into wet tea powder with a smooth texture. The temperature of wet powdered tea shows that the result on the 1st day of 28.75 ° C increased on the 2nd day, which is 29.5 ° C but does not exceed the standard factory regulation and there is no over at the powder temperature due to the temperature regulation by the humidifier. Color analysis with the number of 30 untrained panelists has a real difference with other untrained panelists with a flat category of tea powder color treatment A, B, C, D. Identification of the performance efficiency of the tea leaf milling machine shows that there is a decrease in performance in tearing tea leaves for 7 days due to the high time wasted on idling minor stoppages at the time of the previous mill and reduced speed losses on roll teeth or TPI (Teeth Per Inch).